Estudo sobre os determinantes do investimento na indústria de transformação brasileira: análise setorial para o período de 1996 a 2012 - Nunes, Stephano Hertal Farias [UNESP] (2015)
Brazil experienced an industrialization process that aimed to replace imported products for goods produced domestically. This fact, which occurred deliberately by the state over three decades (1950-1970), named industrialization by import substitution (IIS). Industrialization ensued gradually: first the installation of the industrial park of consumer goods, durable consumer goods and subsequently the installation of capital and intermediate goods industry. No relative stability for the construction of minimally reliable expectations about the future, the 1980s, known as the lost decade, is seen as a period of slowing economic activity and falling investment. The succession of economic plans implemented in order to curb inflation only succeeded with the plan Real, in 1994. Mainly from this year investment rates in Brazil has remained below 20% of gdp, one of the reasons given for the weak economic growth. The objective of this work is to build a model that describes the impact of economic variables on the decision to invest in new and stable period of the brazilian economy. This research is part of a small, but growing number of studies dedicated to understanding the manufacturing sector in the optical industry, highlighting the heterogeneity created throughout the history of industrialization process. Through a long process of conversion of data, it was possible to work with statistics PIA (IBGE) from 1996 to 2012 (last year released until the preparation of the work). The research is organized into sections theoretical character, historical and empirical. The first section is in charge of presenting the main theories about the determinants of investment. The second section will present Brazil's industrialization process and the evolution of economic variables and sector investment in the manufacturing industry. In the third and final section are estimated empirical models to examine the ...